Lipid-Polymer Hybrid Nanoparticles as a Smart Drug Delivery System for Peptide/Protein Delivery - Alharith A. A. Hassan; Eslam Ramadan; Katalin Kristó; Géza Regdon; Tamás Sovány (Pharmaceutics, 2025)
The efficient oral delivery of therapeutic proteins and peptides poses a tremendous challenge due to their inherent instability, large molecular size, and susceptibility to enzymatic degradation. Several nanocarrier systems, such as liposomes, solid lipid nanoparticles, and polymeric nanoparticles, have been explored to overcome these problems. Liposomes and other lipid-based nanocarriers show excellent biocompatibility and the ability to encapsulate hydrophobic and hydrophilic drugs; however, they often suffer from poor structural stability, premature leakage of the loaded drugs, and poor encapsulation efficiency for macromolecular peptides and proteins. On the other hand, polymeric nanoparticles are more stable and allow better control over drug release; nevertheless, they usually lack the necessary biocompatibility and cellular uptake efficiency. Recently, lipid-polymer hybrid nanoparticles (LPHNs) have emerged as an advanced solution combining the structural stability of polymers and the biocompatibility and surface functionalities of lipids to enhance the controlled release, stability, and bioavailability of protein and peptide drugs. In this review, an attempt was made to set a clear definition of the LPHNs and extend the concept and area, so to our knowledge, this is the first review that highlights six categories of the LPHNs based on their anatomy. Moreover, this review offers a detailed analysis of LPHN preparation methods, including conventional and nonconventional one-step and two-step processes, nanoprecipitation, microfluidic mixing, and emulsification methods. Moreover, the material attributes and critical process parameters affecting the output of the preparation methods were illustrated with supporting examples to enable researchers to select the suitable preparation method, excipients, and parameters to be manipulated to get the LPHNs with the predetermined quality. The number of reviews focusing on the formulation of peptide/protein pharmaceutics usually focus on a specific drug like insulin. To our knowledge, this is the first review that generally discusses LPHN-based delivery of biopharmaceuticals. by discussing representative examples of previous reports comparing them to a variety of nanocarrier systems to show the potentiality of the LPHNs to deliver peptides and proteins. Moreover, some ideas and suggestions were proposed by the authors to tackle some of the shortcomings highlighted in these studies. By presenting this comprehensive overview of LPHN preparation strategies and critically analyzing literature studies on this topic and pointing out their strong and weak points, this review has shown the gaps and enlightened avenues for future research.